Dave and unicorn : Team spirit - Bird, Pip.; O'Connell, David (Children's author) (New York : Imprint, 2020)
"Mira and her unicorn, Dave, tackle their greatest challenge yet: teamwork. Mira is excited for Unicorn School Field Day, even though her unicorn, Dave, loves donuts more than prancing. Mira's teammates are counting on them-especially when the prize for winning Field Day is revealed to be the chance to go on a Magical Rainbow Quest. As Mira struggles to get her UBFF (Unicorn Best Friend Forever) to hurry to the finish line, a series of mysterious mishaps make Mira wonder if everyone is playing fair. Can she and Dave track down who's sabotaging them before they end up in last place?"--Back cover.
4.4
3-6.
3-6
Keywords: Humorous stories; Schools -- Juvenile fiction; Unicorns -- Juvenile fiction; Humorous stories; Schools -- Fiction; Unicorns -- Fiction; School stories; Unicorns -- Fiction; Humorous fiction